KAJIAN SOSIOLOGIS TENTANG RASIONALITAS FORMAL DAN RASIONALITAS SUBSTANTIF DALAM PEMBENTUKAN HUKUM DI INDONESIA SEBAGAI UPAYA UNTUK MEMBANGUN KEPASTIAN HUKUM DAN KEADILAN¹ - meuraksa, elwalad; Agung Arafat Saputra; Rino Dedi Aringga (Rechtsregel : Jurnal Ilmu Hukum, 2025)
This article explores in depth the relationship between formal rationality and substantive rationality in the formation of civil law in Indonesia, using a sociological-legal approach. Formal rationality refers to a legal formation approach oriented toward legal certainty, structure, and logical coherence. In contrast, substantive rationality emphasizes the content of justice, social ethics, and the real-life context of society. In Indonesia, the civil law system, heavily influenced by the Continental European legal tradition, tends to prioritize formal rationality. This is reflected in various civil regulations that emphasize legal procedures and systematic frameworks over the actual needs of society. As a result, the legal norms produced are often elitist and unresponsive to the dynamic development of society. The imbalance between these two forms of rationality hinders the realization of genuine legal justice. This study applies a normative legal method with a qualitative-sociological approach, supported by literature studies and legal document analysis. It examines relevant civil law regulations, such as those relating to contract law, family law, and inheritance law, while also considering legal practices that emerge within communities. The findings of the study show that the dominance of formal rationality in civil lawmaking often leads to a lack of substantive values and creates inequality in the application of justice. In many cases, civil law regulations fail to accommodate the uniqueness and complexity of Indonesia’s social life. Therefore, the study recommends integrating a sociological perspective into every stage of civil law legislation, so that the resulting laws are not only formally valid but also substantively just. The integration of formal and substantive rationality is essential to developing a civil law system that is more humane, inclusive, and responsive to the realities of a pluralistic society such as Indonesia.